PENGARUH PEMBERDAYAAN KARYAWAN, DUKUNGAN ORGANISASI DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASIONAL(Studi Pada Karyawan Generasi Milenial di Solo Raya) - Aisyiyah Widiyastuti (Journal Of Business, Finance, and Economics (JBFE), 2021)
ABSTRACT The purpose of this study was to examine and analyze the effect of employee empowerment, organizational support and compensation on organizational commitment to millennial employees in Solo Raya. The sample in this study was 194 millennial generation employees. Sampling in this study used a non-probability sampling design with purposive sampling method. Hypothesis testing in this study uses multiple linear regression. The results of this study indicate that employee empowerment, organizational support and compensation have a positive and significant effect on organizational commitment.Keywords: employee empowerment, organizational support, compensation, organizational commitment.